Mechanism Formation Carbon Dioxide Around Muriah Trough And Bawean Arc, North East Java Basin, Indonesia - Rachmawati, Dwi; Irfree, Baharianto (UIR PRESS, 2025)
CO2 content in natural gas in Muriah Trough and Bawean Arc, North East Java Basin. Understanding the origin and distribution of carbon dioxide is important for the research of natural gas exploration risk. This research uses gas geochemistry to identify the origin of carbon dioxide formation around the Muriah Trough and Bawean Arc. The chemical composition of CO2 and δ13CCO2 was measured in 10 gas samples taken from 6 exploration wells around the Muriah Trough. The results of the analysis indicate the origin of the carbon dioxide and carbon dioxide mechanism around Muriah Trough and Baswean Arc derived from organic and inorganic processes. The process of forming the carbon dioxide mechanism around the Muriah Trough and Bawean Arc is dominated by inorganic processes, presumably derived from the mantle degassing process. The mantle Deggasing process was related to volcanism Muriah and Bawean the Late Miocene-Pliocene.